Perencanaan Bisnis dan Keuangan pada Acara Workshop Kewirausahaan Pimpinan Cabang Aisyiyah Kebumen - Siti Barokah (LPPM Universitas Harapan Bangsa Purwokerto, 2025)
This community service activity aims to improve the entrepreneurial knowledge and skills of the members of the Aisyiyah Kebumen Branch through a workshop entitled “Business and Financial Planning.” The program was designed using a participatory approach involving 32 female participants who are micro-business actors. The implementation method consisted of three stages: preparation, interactive training, and evaluation. The analysis showed a significant improvement in participants’ ability to develop business plans and manage basic financial records. The average pre-test score of 58.4 increased to 87.2 after the training, indicating the effectiveness of hands-on learning methods. Beyond technical competence, the activity also fostered motivation and an entrepreneurial spirit based on Islamic values. The results demonstrated that collaboration between universities and women’s community organizations plays an essential role in strengthening women’s economic independence and empowerment. Therefore, this workshop has provided a tangible contribution to developing independent, productive, and sustainable entrepreneurship at the local community level.